The Influence of Socio-Economic Factors on Community Mental Health - Van Eggerman Reiss; Lohfeld Brown; Sisitsky Sisitsky; Rousseau Russell (Intitute of Computer Science (IOCS), 2021)
This research investigates the multifaceted relationship between socio-economic factors and community mental health. The aim is to discern the influence of income levels, social stigma, and access to mental health services on the mental well-being of individuals within our society. A mixed-methods approach was employed, combining surveys, interviews, secondary data collection, and qualitative data analysis. A diverse sample of participants from various socio-economic backgrounds was included to capture a comprehensive perspective on the subject. The research reveals that socio-economic factors significantly affect mental health outcomes. Individuals with lower income levels experience higher levels of anxiety. Moreover, social stigma surrounding mental health issues negatively impacts an individual's quality of life. Limited access to mental health services is associated with increased rates of depression. This study underscores the vital importance of addressing socio-economic disparities in mental health. It advocates for the reduction of social stigma, the enhancement of mental health care availability, and policies that support financially vulnerable individuals and families. The findings contribute to our understanding of the intricate interplay between socio-economic factors and community mental health, emphasizing the need for a holistic approach to mental well-being in our society